STUDI KAYU ANGIN (Usnea spp.) SEBAGAI BAHAN OBAT TRADISIONAL Studi Kasus: Pasar Tradisional Kota Jakarta - Jannah, Miftahul; Afifah, Nida (Teknosains: Media Informasi Sains dan Teknologi, 2020)
Research into local community knowledge is very important to provide medicinal plant data and can be used as a basis for further research. Usnea is a genus of lichen that is used by Indonesian people in traditional medicine. The people knows Usnea as Kayu Angin. The aim of this study was to record the use of the species of the genus Usnea as traditional herbal medicines in Jakarta’s tradisional market. The study was a part of a project called Hibah Dosen Pemula (PDP) RISTEKDIKTI. Respondents were interviewed using a semi-structured questionnaire . Data were descriptively analyzed based on exploration results and interviews with respondents. The result showed 14 species of Usnea had been founded and were used to treat different ailments. The collection of data and information about the use of Usnea in Jakarta’s tradisional market was firstly recorded and expected could be enriched Usnea data from Java.